Writing and Social Diversity in Late Bronze Age Ugarit - Philip Boyes (Papers from the Institute of Archaeology, 2022)
Writing at Ugarit has received a great deal of scholarly attention for the wide range of languages and writing systems used, and especially for the city’s distinctive alphabetic cuneiform script which accounts for around half of the inscribed material from the site. The vast majority of the rest is in the Akkadian language and logo-syllabic cuneiform script. This written material is, justifiably, usually seen as scribal, in that the vast majority stems from the state bureaucracy and from professional writers formally trained in a curriculum derived from the Mesopotamian cuneiform tradition. However, by using the blanket term ‘scribe’ we risk obscuring potential diversity in who used writing and why. This paper will explore the extent to which we can identify social diversity within writing practices at Ugarit and will focus in particular on three main areas: gender and women’s literacy; social mobility and writing outside the traditional literate establishment; and the relationship between writing and possible minority communities within Ugaritian society.